PUBLIC-PRIVATE PARTNERSHIP DALAM PENGELOLAAN AGROWISATA JOLLONG DI KABUPATEN PATI - Widya Pramanti, Ririh; Zarkasyi Rahman, Amni; Hanani, Retna (Journal of Public Policy and Management Review, 2024)
The tourism potential managed by each region using the APBD as a source of funding is generally insufficient to meet the needs of tourism development. Public-Private Partnership is present as the main strategy in resolving the issue. Through Pati Regency Regional Regulation Number 2 of 2018 concerning the Master Plan for Tourism Development of Pati Regency in 2018-2025, the Pati Regency Government cooperates with PT Perkebunan Nusantara IX to develop Jollong Agro-tourism. The purpose of this research is to know the implementation of the Public-Private Partnership and the factors that influence the implementation of the Jollong Agro-Tourism management. The theory used is an important guideline public-private partnership by Casanova. This study used a descriptive qualitative method by collecting data through interviews and document studies. The research results show that the cooperation between the Pati Regency Government and PTPN IX in the management of Jollong Agro- tourism has been carried out in accordance with the principles of equity, effectiveness, efficiency, and exportability. Things that still need to be evaluated by actors are related to tourist services, community participation in building a positive impression, and the cleanliness of public facilities. The factors that support the implementation of cooperation are the same mission and goals, clarity of roles and responsibilities, and actors who need each other. Meanwhile, the obstacles are the target population of visits and the pandemic. The recommendations given are the involvement of pokdarwis, procurement of socialization, implementation of employee training, and optimization of tourism promotion.